IMPLEMENTASI WANPRESTASI TERHADAP PERJANJIAN KREDIT MACET DI KOPERASI CATUR MEGA SEDANA - Putra, Ida Bagus Cahya Rama; Sudiana, Anak Agung Kt (Jurnal Hukum Mahasiswa, 2024)
A cooperative is a legal entity established by individuals or other cooperatives that provides savings and loan services to the public. Currently, credit unions for savings and loans are becoming increasingly popular among credit seekers. In the case of the Catur Mega Sedang Cooperative, a breach of contract occurred when a debtor defaulted on their obligations, failing to fulfill their promised repayment duties. The issue faced by the Catur Mega Sedana Cooperative stemmed from the debtor’ s negligence in fulfilling their loan repayment obligations. The research employed an empirical legal research method, utilizing theories of Legal Systems, Contract, and the Functions of Law. The study demonstrates that although credit provision and regulation are effectively implemented in accordance with relevant laws and regulations, insufficient diligence in financial analysis or the application of the 5C principles in credit provision by the LPD led to non-performing loans. The Catur Mega Sedana Cooperative resolves these non-performing loan disputes through non- litigious means.